SU(3)c⊗SU(4)L⊗U(1)X without exotic electric charges (2004)
ABSTRACT: We present an extension of the standard model to the local gauge group SU(3)c⊗SU(3)L⊗U(1)X with a family nonuniversal treatment and anomalies canceled among the three families in a nontrivial fashion. The mass scales, the gauge boson masses, and the masses for the spin 1/2 particles in the model are analyzed. The neutral currents coupled to all neutral vector bosons in the model are studied, and particular values of the parameters are used in order to simplify the mixing between the three neutral currents present in the theory, mixing which is further constrained by experimental results from the CERN LEP, SLAC Linear Collider, and atomic parity violation.